Liste aller Gutachtenden des Jahres 2023 (Kriminologie - Das Online-Journal, 2023)
KrimOJ applies a double-blind peer review process, which means that throughout the review the identities of both reviewers and authors are concealed from each other. Reviewers are not paid and work as part of the academic community. By listing them here, we extend our gratitude for their work.